Sarcomatoid carcinoma of the urinary bladder: the final common pathway of urothelial carcinoma dedifferentiation - Cheng, Liang; Zhang, Shaobo; Alexander, Riley; Maclennan, Gregory T; Hodges, Kurt B; Harrison, Beth T; Lopez-Beltran, Antonio; Montironi, Rodolfo (The American journal of surgical pathology, 2011)
Sarcomatoid carcinoma of the urinary bladder is an unusual malignancy composed of both carcinomatous and sarcomatous components. It is an aggressive tumor that presents at an advanced stage and confers a much poorer prognosis than conventional urothelial carcinoma. The proper nomenclature and histogenesis of these tumors have been subjects of debate for some time. There is an emerging consensus that sarcomatoid carcinoma is the most appropriate term for these neoplasms. The recent World Health Organization classification has applied this term to all tumors showing morphologic and/or immunologic evidence of both malignant epithelial and mesenchymal differentiation. Such tumors have been postulated to represent either multiclonal collision tumors or monoclonal cancers with divergent differentiation; recent molecular studies favor the latter theory. In this study, we discuss the nomenclature, clinical features, pathology, differential diagnosis, molecular genetics, and histogenesis of sarcomatoid carcinoma. We emphasize the importance of molecular genetic studies in providing insight into the histogenesis of this neoplasm. Sarcomatoid carcinoma seems to represent the final common pathway of urothelial carcinoma dedifferentiation.